Laparoscopic cholecystectomy in pregnancy: An Australian retrospective cohort study. (June 2015) - Paramanathan, Ashvin; Walsh, Sam Zachary; Zhou, Jieyun; Chan, Steven
Abstract: Introduction: Biliary tract disease is a common non-obstetric surgical presentation during pregnancy. Although small international series demonstrate favourable outcomes following laparoscopic cholecystectomy (LC) during pregnancy, there is a paucity of Australian data to complement these findings. Method: Between 1st January 2003 and 30th June 2013, all patients undergoing planned LC during pregnancy at Western Health were retrospectively identified. Results: Twenty-two patients underwent planned LC with 3 (13%) cases converted to open surgery. The median maternal age was 31 years (27.8–36) with an estimated median gestational age (EGA) of 19.5 weeks (16.5–23.5). Eighteen (82%) cases were performed during the second trimester. Nine (40%) patients had 2 or more hospital admissions for similar presentations. Twelve (54%) were performed as index cases. Operative indications included 12 (54%) with recurrent biliary colic, five (22%) with acute cholecystitis and 3 (14%) with gallstone pancreatitis. Median operating time for completed LCs was 65 min (60–95). Intra-operative cholangiogram was performed in seven (32%) cases, 5 (71%) of which employed protective uterine lead shielding. There was no fetal loss or uterine injury. Median hospital stay was 3 days (2–7) for completed LCs. Major morbidity occurred in 2 (10%) completed LCs that required a return to theatre. Five (23%) births were lost to follow up. The median time to delivery post-surgery was 13 weeks (11–15). Two (12%) preterm deliveries occurred, with subsequent neonatal complications. Conclusion: Antenatal laparoscopic cholecystectomy demonstrated comparably safe outcomes. Increasing its utilization to manage symptomatic cholelithiasis during pregnancy may be considered. Highlights: Biliary tract disease is a common non-obstetric surgical presentation during pregnancy. There is scarce Australian data to support antenatal laparoscopic cholecystectomy. Twenty-two patients underwent laparoscopic cholecystectomy during pregnancy. No mortality and comparable morbidity was demonstrated. Our results support early laparoscopic cholecystectomy during pregnancy.